Sulfate reduction in acetate- and ethanol-fed bioreactors: Acidic mine drainage treatment and selective metal recovery - Yurtsever, Adem; Yildiz, Mujgan; Yilmaz, Tulay; Arzum, Cemile Seyma; Kaksonen, Anna H.; Ucar, Deniz (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Acid mine drainage is the outflow from a mining site which contains high sulfate and metal concentrations and low pH. Appropriate disposal of this drainage relies on the removal and preferably recovery of heavy metals and neutralizing pH. Sulfidogenic electron donor oxidation generates alkalinity which increases water pH. In this study, sulfate reduction was studied comparatively in two up-flow reactors fed with acetate and ethanol, respectively. Reactors were operated in parallel for 148 days and the influent 2000 mg/L sulfate was decreased to 51 +/- 7 and 31 +/- 6 mg/L in ethanol and acetate fed reactors, respectively. With the produced hydrogen sulfide, metal precipitation in a simulated AMD containing both copper and nickel was studied. Copper was precipitated at low pH (pH < 2) by the gaseous hydrogen. Cu precipitation was completed within 35 min and Ni did not precipitate during Cu removal. Nickel recovery was studied at higher pH values (pH = 8) using reactor effluent containing dissolved sulfide and alkalinity. Mineralogical characterization of the precipitates using X-ray diffraction indicated that CuS and NiS were precipitated selectively in the two metal removal stages.
Keywords: Sulfate reduction; Up-flow reactor; Copper; Nickel; Precipitation; Acid mine drainage